MATH EDUCATIONAL GAME TO ENHANCE JUNIOR HIGH SCHOOL STUDENTS’ ALGEBRAIC THINKING - Lilik Ariyanto; Muhammad Prayito; Syahru Romadhon; Achmad Buchori (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
Students in the 21st century require training in solving real-world problems involving algebraic thinking through the use of technology in order to adapt effectively to their environment. This study aims to develop a math education application on algebra material that is valid, practical and effective for improving algebraic thinking skills. This type of research is development research with the ADDIE model. The research instruments employed in this study were: 1) expert validity, 2) an algebra test sheet, and 3) a questionnaire to gather students’ reactions to the developed educational game. Validity comprised game validity and content validity, aiming to obtain a valid and usable mathematics educational game. The data was analysed descriptively through the results of the educational game validity sheet. Meanwhile, the effectiveness of the educational game was observed through the results of the algebra ability test using a t-test. Furthermore, through the student response questionnaire, the researcher was able to ascertain the practicality of using the mathematics educational game. The results of this study indicate that the results of expert validation: (1) Feasible based on the validation results of media experts and material experts; (2) Practical based on student response questionnaires with excellent criteria; and (3) Effective where the average learning outcomes of the experimental class are better than the control class, a classical completeness of 81.14% was attained, positively correlated with learning interest, which in turn contributed to learning outcomes of 72.7%.Abad 21 mengharuskan siswa untuk terlatih dalam memecahkan masalah kehidupan nyata yang berkaitan dengan pemikiran aljabar menggunakan teknologi agar mampu beradaptasi dengan baik dilingkungannya. Penelitian ini bertujuan untuk mengembangkan aplikasi pendidikan matematika pada materi aljabar yang valid, praktis dan efektif untuk meningkatkan kemampuan berpikir aljabar. Jenis penelitian ini adalah penelitian pengembangan dengan model ADDIE. Instrumen penelitian yang digunakan adalah: 1) validitas ahli, 2) lembar tes aljabar, 3) angket yang berisi reaksi siswa kepada game edukasi dikembangkan. Validitas terdiri dari validitas game edukasi dan validitas materi bertujuan untuk mendapatkan game edukasi matematika yang valid dan layak digunakan. Data tersebut dianalisis deskriptif melalui hasil lembar validitas game edukasi. Sedangkan, keefektifan game edukasi dilihat dari hasil tes kemampuan aljabar dengan menggunakan perhitungan uji-t. Selanjutnya, peneliti melalui angket respon siswa peneliti dapat mengetahui kepraktisan penggunaan game edukasi matematika. Hasil penelitian ini menunjukkan bahwa hasil validasi pakar: (1) Layak berdasarkan hasil validasi pakar media dan ahli material; (2) Praktis berdasarkan kuesioner respons siswa dengan kriteria unggulan; dan (3) Efektif dimana rata-rata hasil pembelajaran kelas eksperimen lebih baik dari kelas kontrol, persentase keuntasan klasikal adalah 81,14%, dan ada pengaruh positif minat belajar dengan hasil pembelajaran sebesar 72,7%.